Christian Doctrines and Practices of Solidarity in the 1960's - (:unkn) unknown (My University, 2012)
This article is intended to be a contribution to the analysis of the politics of cooperation -the doctrine and the practices - of the French Confederation of Christian Workers (CFTC)/ which became the French Democratic Confederation of Labor (CFDT) in 1964, shortly before many African countries gained independence in 1960. The analysis is conducted on three complementary axes. First the institutional practices of cooperation are explored: financing policies and the educational policy which was the heart of the program. It also attempts to explain the sources of the solidarity doctrine put in place by the CFTC/CFDT and by the Christian International to which it was affiliated. Finally, what can be called different types of solidarity via network, different kinds of help given to individuals, largely related to links of friendship, are examined.
Keywords: African Research